Direct displacement-based design of the linked column steel frame System, Part 1: Modeling and yield drift evaluation. (June 2021) - Tazarv, Javad; Mohebkhah, Amin
Abstract: The linked column frame (LCF) system is a load resisting system in which replaceable link beams are used to provide the desired structural behavior at various performance levels. The optimal performance of this system can be achieved by controlling the successive yielding pattern of its structural fuse elements using performance-based seismic design methods. This paper derives some analytical relationships for the yield drift estimation of the LCF system required to its direct displacement-based design developed in the companion paper. The obtained results show the high accuracy of the proposed relationships to estimate the yield drift of the LCF system.